2018
DOI: 10.1016/j.jallcom.2018.06.357
|View full text |Cite
|
Sign up to set email alerts
|

High-hole mobility Si1-Ge (0.1 ≤ x ≤ 1) on an insulator formed by advanced solid-phase crystallization

Abstract: The grain size and hole mobility of polycrystalline Si1-xGex thin films formed on glass by solid-phase crystallization were significantly improved after preparing the amorphous precursors by heating the substrate. By just controlling the deposition temperature of the precursors (50-350 °C) for each SiGe composition, the grain size reached over 2 μm across the whole composition range. Reflecting the enlargement of the grain size, the hole mobility values were improved by approximately one order of magnitude. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…29 We recently found that the atomic density of amorphous Ge (a-Ge) significantly influenced subsequent SPC. [30][31][32] By using a densified a-Ge on a GeO 2 underlayer, we fabricated a poly-Ge layer with a hole mobility of 620 cm 2 /V s, 33 which greatly exceeds that of bulk-Si (430 cm 2 /V s). These achievements initiated the prospect of the development of inversion-type poly-Ge n-MOSFETs that surpass Si-MOSFETs.…”
mentioning
confidence: 99%
“…29 We recently found that the atomic density of amorphous Ge (a-Ge) significantly influenced subsequent SPC. [30][31][32] By using a densified a-Ge on a GeO 2 underlayer, we fabricated a poly-Ge layer with a hole mobility of 620 cm 2 /V s, 33 which greatly exceeds that of bulk-Si (430 cm 2 /V s). These achievements initiated the prospect of the development of inversion-type poly-Ge n-MOSFETs that surpass Si-MOSFETs.…”
mentioning
confidence: 99%
“…This behavior is consistent with the metal-free SPC of SiGe, where the LE temperatures are 100-300 °C lower than the SPC temperatures. [100][101][102][103] For all metal species and x, the LE temperatures reach 500 °C, which is the heat resistance temperature of engineering plastic films. The LE temperature is particularly low for Ge-Zn systems, which allows for the use of generalpurpose plastic films.…”
Section: Growth Propertiesmentioning
confidence: 99%
“…In general, undoped polycrystalline SiGe layers exhibit p-type conduction because of acceptor defects in Ge. [102,116,117] The addition of As in Zn, Ag, and Au allows n-type conduction control of SiGe layers at low x (≤0.3), though it is difficult for Ge-rich SiGe layers with a high density of acceptor defects (Figure 6c). Thus, the LE with impurity-doped metals enables the low-temperature synthesis of p-type Si 1-x Ge x with the whole x range, while the n-type is at low x (≤0.3).…”
Section: Electrical and Thermoelectric Propertiesmentioning
confidence: 99%
“…With an 'on-insulator' structure, the performance of Ge electronic devices can be further improved through reducing parasitic capacitance and leakage current. Many techniques have been developed to obtain Ge-on-insulator (GOI) platforms such as wafer bonding [3], smart-cut [4], solid-phase crystallization [5,6], and Ge condensation [7,8]. Among them, Ge condensation, which uses cyclic oxidation and annealing of low-Ge-content SiGe-on-insulator (SGOI) material at high temperature (≥ 900 • C), can be used to fabricate high quality SGOI with a desired Ge content up to 1.0.…”
Section: Introductionmentioning
confidence: 99%